Shank3-mutant mice lacking exon 9 show altered excitation/inhibition balance, enhanced rearing, and spatial memory deficit - Lee, Jiseok; Chung, Changuk; Ha, Seungmin; Lee, Dongmin; Kim, Do-Young; Kim, Hyun; Kim, Eunjoon (Frontiers in Cellular Neuroscience, 2015)
Shank3 is a postsynaptic scaffolding protein implicated in synapse development and autism spectrum disorders. The Shank3 gene is known to produce diverse splice variants whose functions have not been fully explored. In the present study, we generated mice lacking Shank3 exon 9 (Shank3∆9 mice), and thus missing 5 out of 10 known Shank3 splice variants containing the N-terminal ankyrin repeat region, including the longest splice variant, Shank3a. Our X-gal staining results revealed that Shank3 proteins encoded by exon 9-containing splice variants are abundant in upper cortical layers, striatum, hippocampus, and thalamus, but not in the olfactory bulb or cerebellum, despite the significant Shank3 mRNA levels in these regions. The hippocampal CA1 region of Shank3∆9 mice exhibited reduced excitatory transmission at Schaffer collateral synapses and increased frequency of spontaneous inhibitory synaptic events in pyramidal neurons. In contrast, prelimbic layer 2/3 pyramidal neurons in the medial prefrontal cortex displayed decreased frequency of spontaneous inhibitory synaptic events, indicating alterations in the ratio of excitation/inhibition (E/I ratio) in the Shank3∆9 brain. These mice displayed a mild increase in rearing in a novel environment and mildly impaired spatial memory, but showed normal social interaction and repetitive behavior. These results suggest that ankyrin repeat-containing Shank3 splice variants are important for E/I balance, rearing behavior, and spatial memory.